IMPLEMENTASI NILAI-NILAI PENDIDIKAN ISLAM DAN KEWIRAUSAHAAN DI SEKOLAH DASAR JAWA TENGAH TINJAUAN HISTORIS DAN ANALISIS EMPIRIS - Rizki Diana; Muhlisin Muhlisin; Bambang Sri Hartono (TA'LIM : Jurnal Studi Pendidikan Islam, 2026)
This study examines the implementation of Islamic educational values integrated with entrepreneurship (edupreneurship) in elementary schools in Central Java, considering the importance of preparing a generation that is not only morally virtuous but also possesses an entrepreneurial spirit from an early age. The research objectives are to analyze historical patterns of Islamic value-based edupreneurship development, identify implementation strategies, and evaluate program effectiveness on character formation and entrepreneurial competencies of elementary students. The study employs a mixed-methods approach with an embedded concurrent design. Research subjects include 240 students in grades 4-6, 24 teachers, and 12 principals from 12 Islamic elementary schools in Semarang, Surakarta, and Pekalongan selected through purposive sampling. Research instruments consist of entrepreneurial competency questionnaires, observation guides, and in-depth interview guides. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were analyzed using thematic analysis and data triangulation techniques. Results indicate that Islamic value-based edupreneurship implementation in Central Java elementary schools has developed since the 2010s through curriculum integration, market day programs, and student cooperatives. Dominant Islamic values implemented include honesty (amanah), hard work (itqan), and responsibility (mas'uliyah). There were significant increases in student creativity (78.5%), independence (72.3%), and entrepreneurial awareness (65.8%). This study recommends strengthening parent-school collaboration, developing edupreneurship modules based on local wisdom, and supportive policies from local governments for program sustainability.